The ecological mushrooms of Dominica - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
An entrepreneurial couple in Dominica in the Caribbean have developed a way to farm mushrooms organically. Mushroom gathering on the island has long been a tradition. Since the eighties the Luke family tried through trial and error to find ways to...